Aplikasi Pencarian Tempat Wisata Berbasiskan GPS dengan Metode Radius dan Rating - Budi Yulianto; Rita Layona (Bina Nusantara University, 2015)
Tourist place navigation application becomes more important for travelers, especially backpackers. Previous research had produced applications which can only show the route from the position of traveler to tourist place with map shown. The goal of the research is to use the radius and rating method that is still rare in the community to navigate tourist place. Output of the research is a GPS-based application that can display the search results of tourist sites based on rating and radius method, route from the traveler to the destination place, and description of the place. Development method used waterfall that contained user requirement, analysis, design, coding and testing, implementation, and maintenance. Conclusion of the research has shown that the developed application provided convenience in searching tourist places based on radius and rating, displaying route, and description of tourist places.